“Flying Higher”: understanding the meanings given to scientific initiation in Brazil - Oliveira, Adriano de (2014)
This article discusses how Brazil’s Institutional Scholarship Institutional Scholarship Program for Scientific Initiation in High School (PIBIC-EM), which is designed to encourage young people to enter science careers and to increase the celerity of scientific training, is understood by the grantees as a mechanism that facilitates their access to higher education and, consequently, to improved class status. The authors consider the fundamental theoretical framework concerning the analysis of public policies on careers in science, as well as relevant ideas regarding the role of education in the acquisition of cultural and relational capital. The authors present the idea that during participation in the program young people develop modus operandi that break certain class conditionings, anticipating futures that otherwise would be difficult for them to envision. The article is based on a study that included documentary analysis, as well as in-depth interviews with grantees in four public schools and seven supervisors in the PIBIC - EM at the Federal University at Santa Catarina (UFSC) campuses of Florianópolis, Araranguá and Curitibanos in southern Brazil . The conclusions point out the positive influence of the program in strengthening opportunities for professional trajectories for students from low-income families